PENERIMAAN WAJIB PAJAK PADA AWAL IMPLEMENTASI E-FAKTUR PAJAK BERBASIS DESKTOP APPLICATION - Safitra, Adhetiya (Jurnal Pajak dan Keuangan Negara (PKN), 2021)
Currently, the tax authorities in Indonesia are active in shifting tax services to an online system. One of these tax services is an e-Tax Invoice. The success of e-government projects such as e-Tax Invoices depends on the reliability of ICT and depends on the community (in this case PKP) as end-users. This study uses a structural equation model to identify the factors that influence the willingness of taxpayers to use online services with models based on the theory of planned behaviour (TPB) and the technology acceptance model (TAM). This study indicates that only perceptions of usability indirectly affect taxpayers’ encouragement to use the application.